2021
DOI: 10.3390/ijms222413188
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic and Lipidomic Profiling Reveals Novel Biomarkers of Efficacy for Benfotiamine in Alzheimer’s Disease

Abstract: Serum metabolomics and lipidomics are powerful approaches for discovering unique biomarkers in various diseases and associated therapeutics and for revealing metabolic mechanisms of both. Treatment with Benfotiamine (BFT), a thiamine prodrug, for one year produced encouraging results for patients with mild cognitive impairment and mild Alzheimer’s disease (AD). In this study, a parallel metabolomics and lipidomics approach was applied for the first exploratory investigation on the serum metabolome and lipidome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Metabolomics is an emerging approach in life science and precision medicine for biomarker discovery in various neurodegenerative diseases such as MS.(Bhargava and Calabresi 2016; Noga et al 2012) Previous studies showed that specific altered metabolites and lipids in plasma samples varied with AD progression. (Bhawal et al 2021) The metabolomic profile of the produced plasma patterns revealed many significantly changing metabolites in different MS types particularly RRMS and SPMS (red dots in Supplementary Figure 13 ) in all the layers. For example, it has been reported that glutamate may be related to inflammatory and neurodegenerative processes evident in MS.(Kostic et al 2013; Pitt et al 2000) We have also found that glucoheptonic acid metabolite is significantly different in layers one and two of the produced plasma patterns within the MagLev system.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is an emerging approach in life science and precision medicine for biomarker discovery in various neurodegenerative diseases such as MS.(Bhargava and Calabresi 2016; Noga et al 2012) Previous studies showed that specific altered metabolites and lipids in plasma samples varied with AD progression. (Bhawal et al 2021) The metabolomic profile of the produced plasma patterns revealed many significantly changing metabolites in different MS types particularly RRMS and SPMS (red dots in Supplementary Figure 13 ) in all the layers. For example, it has been reported that glutamate may be related to inflammatory and neurodegenerative processes evident in MS.(Kostic et al 2013; Pitt et al 2000) We have also found that glucoheptonic acid metabolite is significantly different in layers one and two of the produced plasma patterns within the MagLev system.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these results, most PCs were upregulated in the plasma of APP/PS1 mice in the present study. In fact, researches on the levels of PCs in AD were not uniform and the results were somewhat controversial ( Toledo et al, 2017 ; Huo et al, 2020 ; Bhawal et al, 2021 ). These contrary findings could arise by diverse functions of different PCs, which can be responsible for the minority of decreased PCs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For the lipidomic analysis, acquired MS/MS data were processed using Thermo Scientific LipidSearch 4.2 software for peak detection, lipid annotation, peak alignment, and relative quantitation ( Bhawal et al, 2021 ). The main parameters were set as follows: precursor tolerance, 5 ppm; product tolerance, 5 ppm; intensity threshold for product ion, 5.0%.…”
Section: Methodsmentioning
confidence: 99%
“…To mitigate the long-term effects of metabolic disorders, healthcare providers rely on a wide range of interventions. These interventions may include lifestyle changes, such as changes in diet and exercise habits, as well as medication to manage symptoms and prevent further health complications [ 6 , 7 ]. In recent years, the development of high-resolution molecular tools has allowed for a more accurate detection and diagnosis of metabolic disorders by examining the leading and lagging indicators in patients.…”
Section: Introductionmentioning
confidence: 99%